Decision Method of Bridge Deck Pavement Maintenance Based on the Decision Maker's Objective. (7th June 2021) - Liang, Xiaofei; Shi, Jun; Li, Zhongmei
Abstract : The performance of reinforced concrete bridge deck pavement will be gradually reduced with the increase of operation time, so the reasonable maintenance measures should be taken to ensure the performance and safety of the bridge structures. The objectives and their hierarchical structures from both state position and enterprise position of the decision makers in bridge engineering decision-making problems were discussed. By the existing deterioration model, this paper studies the bridge operation safety maintenance strategy, establishes the mathematical model of the influence of different degrees of maintenance measures on the structural performance, combines with the cost-benefit theory, establishes the maintenance risk decision criteria for the decision makers with different objectives, and makes the decision on the selection of the bridge deck pavement scheme based on the enterprise position through an example.